Physical Home Food Environment And Its Correlation With Iron And Vitamin C Intake Of Children In Pejagalan - Adhelia Niantiara Putri; Dian Novita Chandra; Luh Ade Ari Wiradnyani; Alfi Rahma Putri; Fitya Safira Birahmatika; Dwi Nastiti Iswarawanti; Lestari Octavia; Hera Nurlita (Media Gizi Indonesia, 2022)
Despite the fact that Indonesia has established nutrition and health measures to prevent childhood malnutrition, more than 70% of children aged 2 to 5 consume less iron than the Indonesian dietary recommendations. Iron deficiency harms children's cognitive and motor development, increase morbidity. Ascorbic acid prevents stomach iron accumulation, inhibiting nonheme absorption. Iron-deficient kids don't eat enough. 65 to 72% of children's daily calories are consumed at home, hence the environment is crucial. The purpose of this study is to see if the iron and vitamin C consumption of children aged 2 to 6 in Pejagalan, North Jakarta, is related to their eating environment. There were 191 samples examined. To assess children's intake, 2x24h food recalls were performed. A modified version of the NHANES CBQ was used to assess the home food environment. For each response, 1 signified "never" and 4 meant "always." SPSS Version 20 was used to perform Spearman correlation and multiple linear regression. The iron and vitamin consumption of the subjects was lower than the estimated average requierement (EAR) for Indonesia. It was shown that people who had more access to fruits and vegetables ingested more iron and vitamin C. Iron consumption was enhanced by fruits, vegetables, sweets, and SSB. Fruit accessibility (p<0.05) and availability (p<0.05) were related to vitamin C consumption. There are a variety of home food environment characteristics linked with the availability and accessibility of food that are related to a child's consumption, particularly of micronutrients